2005
DOI: 10.1111/j.1523-1755.2005.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endoplasmic reticulum (ER) stress in podocyte injury induced by excessive protein accumulation

Abstract: This paper implicates a crucial role for the accumulation of excessive proteins in the podocyte ER in the induction of ER stress and associated podocyte injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 48 publications
2
84
1
Order By: Relevance
“…Previous reports by our and other groups have emphasized a pathogenic role of ER stress in glomerular and tubular epithelial injury. 14,17,20,21 Immunohistochemical analysis in this study showed upregulation of the ER chaperones GRP78 and ORP150 in the glomeruli of rats with antiThy1 nephritis. Furthermore, activation of the PERK pathway, a UPR pathway involved in the downregulation of translation, was also detected in the glomeruli of these rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports by our and other groups have emphasized a pathogenic role of ER stress in glomerular and tubular epithelial injury. 14,17,20,21 Immunohistochemical analysis in this study showed upregulation of the ER chaperones GRP78 and ORP150 in the glomeruli of rats with antiThy1 nephritis. Furthermore, activation of the PERK pathway, a UPR pathway involved in the downregulation of translation, was also detected in the glomeruli of these rats.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated glomeruli were obtained from the experimental rats using a conventional sieving method 17 and homogenized in a sample buffer (0.35 M Tris-HCl [pH 6.8], 10% SDS, 36% glycerol, 5% ␤-mercaptoethanol, and 0.012% bromophenol blue). The obtained test samples (50 g of proteins for each) were electrophoresed on SDS-PAGE and transferred to a polyvinylidene fluoride membrane (Amersham Biosciences, Piscataway, NJ).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Common insults such as the accumulation of advanced glycation end products (AGEs) and the activation of their receptors have been implicated in not only the pathogenesis of DN (Forbes et al 2003, Wendt et al 2003, Tan et al 2010 but also the induction of ER stress (Inagi et al 2005, Cheng et al 2006. Moreover, the accumulation of AGEs within the skin (representing tissue accumulation) also predicts those T1D individuals at a greatest risk of developing nephropathy (Yu et al 2006).…”
Section: Mechanisms Culminating In a Stressed Diabetic Podocyte Ermentioning
confidence: 99%
“…Indeed, ER stress is induced in podocytes when acutely stimulated under both highglucose (Cao et al 2014) and low-glucose (Fujii et al 2006) conditions, and it is apparent that there are regulatory mechanisms to alleviate this stress when podocytes are chronically exposed to hyperglycaemic conditions (Inagi et al 2005). Given that cell survival is promoted through the activation of autophagy in the advent of ER stress induced in mammalian cells in a high-glucose environment (Ogata et al 2006), it is likely that compensatory modifications to the ER could be directly linked to autophagy.…”
Section: Mechanisms Culminating In a Stressed Diabetic Podocyte Ermentioning
confidence: 99%